Localization of Myotoxin I and Myotoxin II from the venom of Bothrops asper in a murine model - Vargas Valerio, Sofía (2021)
Phospholipases A2 (PLA2s) and PLA2-like proteins are significant components of snake venoms. Some of these proteins act as potent toxins causing muscle necrosis, which may lead to amputation in severe envenomings. Fundamental aspects of the mechanism of action of these toxins are still not completely known. Myotoxin-I is a catalytically active Asp49 PLA2 from the venom of Bothrops asper, a medically relevant pit viper from Central America. Myotoxin-II is a catalytically inactive Lys49 PLA2-homolog also present in the venom of this snake. For the first time, the in vivo cellular localization of these myotoxins was studied in mouse skeletal muscle using immunofluorescence. Results showed that after 5 min of injection in the gastrocnemius muscle, both toxins initially interacted with the sarcolemma, and some colocalization with nuclei was already evident, especially for Mt-II. After 3 h of injection, a significant colocalization with the nuclei was observed for both toxins. These in vivo results confirm the importance of the initial interaction of these toxins with the sarcolemma and furthermore highlight the internalization and interaction of the toxins with nuclei during their pathophysiological activities, as observed in recent studies using cell culture.